Evaluation of Critical Thinking Ability with Discovery Lerning Using Blended Learning Approach in Primary School - Mulyanto, Bowo Sri; Sadono, Tri; Koeswanti, Henny Dewi (Universitas Negeri Semarang, 2020)
2013 curriculum suggests an active learning model for the learners. During this COVID-19 pandemic, it should go in line with online learning so the learners’ skills would be upgraded. This research aims to analyze and evaluate the critical thinking skill improvement of the learners taught by e-learning integrated into the discovery learning model. This research is classroom action research. The subjects consisted of the fifth graders of SD Negeri 2 Wonodoyo. There were 36 learners. The applied materials in this research consisted of heat-content science learning. The data were taken by observation and critical thinking skill test of the learners. The technique of analyzing data was N-gain. The obtained results were the learners’ critical thinking skill improvement with the N-gain score, 0.485, categorized as moderate. The improvement occurred due to the discovery using blended learning approach made learners interact in a small group in online learning. Then, teachers could also interact during the learning.